The effect of fire on seed germination of campo rupestre species in the South American Cerrado - Fernandes, Alessandra Furtado; Oki, Yumi; Fernandes, Geraldo Wilson; Moreira, Bruno (Plant ecology, 2021)
Fire is an important disturbance in terrestrial ecosystems and plays a key role in the germination process and seedling establishment of many species. In grassland ecosystems, seeds normally tolerate heat-shocks associated with low intensity fires but are negatively affected by higher heat doses. Additionally, smoke-stimulated germination is not commonly recognized as important in neotropical grasslands. This may result from a negative relationship between the ability to resprout after fire and fire-stimulated germination ability, as many species in these grasslands regenerate well after fire by resprouting. To ascertain the role of heat and smoke in the post-fire germination response of campo rupestre vegetation, we exposed seeds of nine species (that regenerate after fire by resprouting) to various treatments related to fire (heat, smoke, and heat plus smoke) and analysed their germination behaviour. Our results suggest that these species have high seed germination in the absence of specific dormancy breaking conditions and/or that stimulated germination triggered by fire-related cues is not common. Additionally, while seeds from some species can withstand temperatures of 80 °C for 5 min without affecting germination, most species are negatively affected by higher heat doses. However, our results suggest an important role of smoke enhancing germination rate (speed) of campo rupestre species. In view of the characteristics of campo rupestre environmental conditions and vegetation, we provide a novel outlook of enhanced germination rate by smoke as an important mechanism for seed regeneration after fire of campo rupestre’s species that resprout, particularly for seeds resulting from post-fire seed dispersion.